Development of water-ethylene glycol based graphene nanoplatelets/cellulose nanocrystal hybrid nanofluid as radiator coolants and its performance evaluation - Madderla, Sandhya (2023)
Traditional thermal fluids are incapable of absorbing the significant amount of heat generated by high performance engines. Greater engine performance requires extra consumed fuel, exposing combustion chambers to excessive heat. An automotive cooling system is designed to maintain the engine temperature at optimal levels. With the rapid growth of technology in the automotive industry, there is a need to increase the performance of conventional cooling systems to improve engine performance. Radiator plays a prominent role in increasing the performance of the cooling system. However, there is a demand for higher thermal properties fluid as the transport medium because of the insufficient thermal performance of traditional fluids. Hybrid nanofluids are exceptional heat transfer liquids due to their superior thermal conductivity. An experimental approach to prepare, characterize and stabilize the hybrid nanoparticles (Graphene nanoplatelets and Cellulose nanocrystals-50:50) in the base fluid (Ethylene Glycol-Water-60:40)) and to analyze the thermo-physical properties of the newly developed hybrid nanofluids and this is used as a coolant in automobile radiators. Combining with the coupling effect of two nanomaterials, the prepared hybrid nanofluids confirmed the proper dispersion stability by Zeta potential and UV absorption analysis and also enhanced the thermal conductivity with the increase in the volume concentration from 0.01%-0.2%. The maximum enhancement for thermal conductivity was around 27% attained at 0.2% hybrid nanofluid. With the increase in the particle loading, the viscosity increased but declined with the temperature by 21%. Moreover, the specific heat is decreased with the increment of hybrid nanofluid concentration. The results from the statistical analysis showed 0.2% GNP/CNC hybrid nanofluid as the optimum concentration for radiator application. The experimental results at different flow rates for hybrid nanofluid (0.2% volume concentration) presented a 41.44% improvement for convective heat transfer coefficient as a result of improved thermal conductivity and surface area and 12.34% pressure drop with respect to base fluid, with an increased density and viscosity the Reynolds number increased with the flow rate and obtained value is 3863.55. With the particle loading, the physical characteristics influenced Nusselt number enhancement with 26.77% for the proposed hybrid nanofluid at 7.2 LPM. Further, the size reduction analysis from computational modeling recommended the reduced dimensions for the flat radiator tube (major diameter-0.016m and length-0.24m) for increased heat transfer coefficient at decreased volume concentration (0.01% GNP/CNC). These outcomes show the overall thermal improvement of the radiator cooling system, which can reduce the dimensions (size and weight) of the radiator by the application of a novel hybrid nanofluid. Novel hybrid graphene nanoplatelets/ cellulose nanocrystal-based hybrid nanofluids performed better in automobile applications and are recommended for heat transfer enhancement in automotive industry.